St. Kitts and Nevis : 2009 Article IV Consultation and Request for Emergency Natural Disaster Assistance; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for St. Kitts and Nevis. (IMF Staff Country Reports; Country Report ;, 2009)
The sharp global recession has been taking a toll on the St. Kitts and Nevis economy. The staff report examines the St. Kitts and Nevis 2009 Article IV Consultation and request for Emergency Natural Disaster Assistance. Economic activity has weakened markedly, particularly in tourism and foreign direct investment (FDI)-related construction, the drivers of growth in recent years. The drop-off in tourism receipts, FDI, and other capital flows could lead to a worsening of the balance-of-payments position.